Do Perceptions of Inequality Negatively Affect Interpersonal Trust? - Jacobs, Chandré (School of Economics, 2023)
Most studies that investigate the relationship between interpersonal trust and inequality make use of objective or societal measures such as the Gini coefficient, and the effect of individual assessments of inequality has thus far received much less academic attention. Using data from the Round 5 Afrobarometer survey, I estimate the effect of perceived inequality on interpersonal trust in South Africa. Though the Round 5 Afrobarometer survey does not include an income variable, I construct an asset index using Principal Component Analysis and find that individual perceptions of socio-economic rank deviate from this measure of objective wealth. In line with the general conclusions in the literature, I find that perceived inequality has a negative effect on interpersonal trust and that individuals who believe that their living conditions are either better or worse compared to those of other South Africans' are less likely to express trust in others. This effect is more prominent in rural areas, which suggests that individuals have biased reference groups influenced by their area of residence.